Pathogenesis of murine cytomegalovirus infection in natural killer cell-depleted mice. - Bukowski, J F (1984)
The effect of natural killer (NK) cells on the course of acute and persistent murine cytomegalovirus (MCMV) infection was examined by selectively depleting NK cell activity by inoculation of mice with antibody to asialo GM1, a neutral glycosphingolipid present at high concentrations on NK cells. The dose of MCMV required to cause 50% mortality or morbidity in control C57BL/6 mice dropped 4- and greater than 11-fold, respectively, in mice first treated with anti-asialo GM1. NK cell-depleted mice had higher (up to 1,000-fold) virus titers in their lungs, spleens, and livers at days 3, 5, 7, and 9 postinfection. Spleens and livers of control mice were virus-free by day 7 postinfection, and their lungs showed no signs of active infection at any time. In contrast, MCMV had disseminated to the lungs of NK cell-depleted mice by day 5, and these mice still had moderate levels of virus in their lungs, spleens, and livers at day 9. Markedly severe pathological changes were noted in the livers and spleens of NK cell-depleted, MCMV-infected mice. These included ballooning degeneration of hepatocytes and spleen necrosis. MCMV-infected, NK cell-depleted mice had severe spleen leukopenia, and their spleen leukocytes exhibited a significantly lower (up to 13-fold) response to the T cell mitogen concanavalin A when compared with those of uninfected and MCMV-infected controls. It appeared that NK cells exerted their most potent antiviral effect early in the infection, in a pattern correlating with interferon production and NK cell activation; treatment with anti-asialo GM1 later in infection had no effect on virus titers. The relative effect of NK cell depletion on MCMV pathogenesis depended on the injection route of the virus. NK cell depletion greatly augmented MCMV synthesis and pathogenesis in mice inoculated either intravenously or intraperitoneally but had no effect on the course of disease after intranasal inoculation, at any time point examined. One month after intraperitoneal inoculation of virus, NK cell depletion resulted in a six- to eightfold increase in salivary gland virus titers in persistently infected mice, suggesting that NK cells may be important in controlling virus synthesis in the salivary gland during persistent infection. This treatment did not, however, induce dissemination of virus to other organs. These data support the hypothesis that NK cells limit the severity, extent, and duration of acute MCMV infection and that they may also be involved in regulating the persistent infection.